EXPERIMENTAL PRESERVATION OF SARDINES (SARDINELLA LONGICEPS),USING CHLORTETRACYCLINE. - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2016)
Effects of dips in 10 and 50 ppm Chlortetracycline solution on the storage-life of sardines in ice have been studied. 5 ppm-CTC-ice in conjunction with dip in 10 ppm CTC-solution has also been tried. CTC-treatment considerably reduced bacterial number and gave a better appearance to the fish. The high fat content in sardines resulted in rapid development of rancidity. CTC has been found to have no control on the development of rancidity. Hence, CTC treatment of sardines is found to be of limited advantage in extending the storage -life of the fish in ice.